Assessing the Impact of Environmental Toxicants on Public Health in Nigeria: An Epidemiological Study - Essiet, Akanimo Gordon; Gordon, Anietie Akanimo; Mkpan, Smart Benjamin; Abok, Janet Ayuba; Sunday, Serah Temitope (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Environmental toxicants present considerable public health challenges, particularly in developing countries such as Nigeria. This epidemiological study investigates the link between environmental toxicants and health outcomes, examining toxicant types, exposure pathways, and their associated health effects. Employing a cross-sectional design, the study randomly selected participants and environmental samples from urban and rural regions. Data were gathered using questionnaires, environmental sampling, and laboratory analysis. Results indicated alarming levels of heavy metals (lead, mercury, cadmium), pesticides, and industrial chemicals (PAHs, PCBs) in soil, water, and air. Significant correlations were observed between these toxicants and chronic diseases, notably respiratory ailments linked to lead and PAHs, and neurological disorders associated with mercury and pesticides. Urban areas showed higher concentrations of industrial chemicals, correlating with elevated cancer and respiratory disease rates, while rural regions exhibited increased pesticide levels, correlating with respiratory and neurological issues. These results highlight the pressing need for robust regulatory frameworks and public health strategies to address the impact of environmental toxicants.